Targeting NADPH oxidase-driven oxidative stress in diabetic cardiomyopathy: mechanisms and therapeutic perspectives - Zilv Ye; Zilv Ye; Sutong Wang; Zhengdong Wan; Birun Huang; Jiawei Guo; Jiawei Guo (Frontiers in Pharmacology)
Diabetic cardiomyopathy (DCM) is a major complication of diabetes mellitus, characterized by microvascular dysfunction and progressive structural and functional deterioration of the heart. A central driver of DCM pathogenesis is chronic oxidative stress (OS), primarily resulting from excessive production of reactive oxygen species (ROS) under hyperglycemic conditions. Among the various ROS sources, the NADPH oxidase (NOX) family of enzymes plays a pivotal role in initiating and sustaining oxidative damage. NOX-mediated ROS production contributes to myocardial inflammation, apoptosis, fibrosis, and remodeling, through multiple signaling pathways, including NF-κB, TGF-β/Smad, MAPK, and PI3K/Akt cascades. Despite growing recognition of NOX enzymes as crucial mediators in DCM, therapeutic options specifically targeting NOX-driven oxidative stress remain limited. In this comprehensive review, we summarize current insights into the mechanisms by which NOX regulates cardiac pathology in DCM, highlight the crosstalk between NOX activity and downstream molecular pathways, and discuss potential pharmacological interventions aimed at restoring redox homeostasis. Emerging strategies, such as selective NOX inhibitors, antioxidant therapies, and agents modulating signaling transduction, offer promising avenues for mitigating oxidative injury and improving cardiac function. Furthermore, we emphasize the importance of developing isoform-specific NOX inhibitors to achieve greater efficacy and safety in clinical applications. By providing a detailed overview of NOX-dependent oxidative stress in DCM and associated therapeutic approaches, this review aims to foster further research and innovation toward targeted treatments for diabetic cardiomyopathy.